Pengembangan Modul Elektronik pada Pembelajaran Search Engine Marketing (SEM) dengan Metode Research and Development (R&D) (Studi pada: SMK PGRI 3 Malang) - Ricky Nourman Alfaried; Retno Indah Rokhmawati; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
This study aims to develop an electronic module that suits the needs and can improve student learning outcomes in Search Engine Marketing (SEM) Online Business subjects at SMK PGRI 3 Malang. The development of electronic modules is carried out using the Research and Development (R&D) method. The developed module applies multimedia principles including Contiguity principle by placing pictures and explanations on one page, Signaling principle by marking special points, Coherence principle by adding materials related to the learning objectives only, and Redundancy principle by reducing explanations or unneeded media. The application of multimedia principles obtained a very good validation level from media experts with an average score of 4.00. Tests using a questionnaire were conducted to material experts, media experts and students to determine the validity of the electronic module. From the testing process, an average total score of 3.50 was obtained with a very good validation level. The Paired Sample T-Test test is used to measure the success rate of implementing the electronic module which is carried out by combining the students' pre-test and post-test scores. This test results in a significance value of 0.000 which is less than 0.05, so there is an increase in the value of learning outcomes obtained by students between before the application of the electronic module (pre test) and after the application of the electronic module (post test).